The Development of a Property Management System for MrPropertyMan - Kamarulzaman, Hajar Munirah; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2025)
The increasing reliance on internet technologies for property transactions highlights the need for a centralized and efficient real estate management system. This study aims to develop the MrPropertyMan Property Management System, a web-based platform designed to streamline operations and improve user experience for admin, agents, and customers. The system uses an object-oriented design approach and adopts the Rapid Application Development (RAD) methodology, integrating modules such as property management, financial analysis, booking, and communication tools. Key findings indicate that the Budget Analysis Module, utilizing a decision tree algorithm, enhances property recommendations based on financial criteria. At the same time, secure user authentication and real-time data updates optimize decision-making. The system reduces inefficiencies and improves workflow, enhancing productivity and customer satisfaction. Future work could explore incorporating artificial intelligence for predictive analytics and expanding functionalities to support larger-scale operations.